Service Delivery and Customer Satisfaction in the Telecom Sector of Kathmandu - KC, Sushant; Upadhyaya, Subika; Neupane, Sujina; Adhikari, Tapascharya Prasad; Tamang, Tista (International Journal of Atharva, 2025)
Background: In the competitive telecom sector of Kathmandu Metropolitan City, service delivery quality is a critical determinant of customer satisfaction and loyalty. Factors such as network quality, pricing, and customer support significantly influence user perceptions, yet the specific nature of these relationships requires empirical investigation in this context.Objectives: This study aims to assess telecommunication service delivery and examine its relationship with customer satisfaction, focusing on the key factors of product/service quality, pricing strategies, and customer service.Methods: Adopting a positivist philosophy and a quantitative methodology, this study employed a descriptive research design. Data was collected via a structured questionnaire from 209 telecom users in Kathmandu Metropolitan City. Descriptive statistics and Pearson correlation analysis were used to analyze the data.Findings: The results indicate significant positive correlations between customer satisfaction and all three independent variables: pricing (r = 0.573, p